The Relationship Between Management Models and Organizational Innovativeness - Buyukbalci, Pinar; Boukari, Zayneb (ACAD CONFERENCES LTD, 2017)
The main purpose of this study is to explore the relationship of four generic management models (as proposed by Birkinshaw, 2012); namely; discovery model, quest model, science model, and planning model; with organizational innovativeness dimensions (as proposed by Wang and Ahmed, 2004); namely, product, market, process, behavioral, and strategic innovativeness. The main premise underlying the research model is that certain principles in each management model impact the emergence of certain innovativeness types. The issue has especially been dealt with its reflections on high tech companies in technoparks. These companies are known for their entrepreneurial and innovative behaviour. However, as to the authors' knowledge, the impact of their management model on their innovativeness capacity has been an understudied issue. Within this framework, following a thorough literature review, hypotheses have been tested by using data from high tech firms in a university technopark. Findings supported the view that different principles of each model significantly impact different organizational innovativeness dimensions. Detailed analyses also put forth interesting results which will open up new fields for further research in this vein.
Keywords: management innovation; innovativeness; management model; high tech firms; innovation; CREATIVITY; TRUST; Business & Economics